Resuscitative Endovascular Balloon Occlusion of the Aorta to Augment Afterload in Non-Traumatic Cardiac Arrest: A Case Report - Boecker, Felix; Gorantla, Kalyan (Journal of Endovascular Resuscitation and Trauma Management, 2018)
We describe the first case report of using a REBOA catheter to augment cardiac afterload in a non-traumatic cardiac arrest patient.